Fact and Fiction in a Robotic Society from a Feminist Perspective - Kiczkowski, Adriana (Zagadnienia Rodzajów Literackich, 2020)
A new narrative of care for the elderly is being constructed in both fiction and our techno-societies that incorporates the use of robots in areas traditionally entrusted to women, reproducing some of the stereotypes historically attributed to them. I propose to analyse representations of robots designed for elder care in the field of science fiction, like in the case of the TV series Real Humans (2012), as well as “real” robots. My aim is to highlight the risks of reproducing gender bias in robotics, where women could continue to perpetuate their role as caregivers. The objective is to show the need to develop a gender perspective in robotics applied to the care of the elderly that will make it possible to change the status quo.